Darkgame [videorecording (DVD)] - Westwick, Ed, 1987-; Stephen, Andrew P.; Tsvetkova, Natalya; Wayne, Lola; Alexander, Rory; Grant, Gary; Johnson, Nail (Russian Roulette Films LTD, 2023)
"A determined detective races to stop an evil game show on the dark web, where each loser dies via a public broadcast."--